1987
DOI: 10.1099/00207713-37-2-166
|View full text |Cite
|
Sign up to set email alerts
|

Erysipelothrix tonsillarum sp. nov. Isolated from Tonsils of Apparently Healthy Pigs

Abstract: A new species, Erysipelothrix tonsillae, is proposed for avirulent Erysipelothrix strains of serotype 7, which is frequently isolated from tonsils of apparently healthy pigs. This species is morphologically and biochemically indistinguishable from the Erysipelothrix rhusiopathiae strains characterized to date. Seven strains of E . tonsillae that belonged to serotype 7 were avirulent for swine, except for strain T-334, which induced a local urticaria1 lesion at the site of inoculation. The 50% lethal dose value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
2
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 14 publications
1
46
2
2
Order By: Relevance
“…The genus Erysipelothrix contains two accepted species, E. rhusiopathiae which include serotypes 1a, 1b, 2, 4, 5,6,8,9,11,12,15,16,17,19,21 and N; E. tonsillarum containing serotypes 3, 7, 10, 14, 20, 22 and 23 [3,4]. Two unclassified Erysipelothrix groups representing serotypes 13 and 18 are also recognized [4].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Erysipelothrix contains two accepted species, E. rhusiopathiae which include serotypes 1a, 1b, 2, 4, 5,6,8,9,11,12,15,16,17,19,21 and N; E. tonsillarum containing serotypes 3, 7, 10, 14, 20, 22 and 23 [3,4]. Two unclassified Erysipelothrix groups representing serotypes 13 and 18 are also recognized [4].…”
Section: Introductionmentioning
confidence: 99%
“…Strains have been isolated from many domestic and wild species, including reptiles, amphibians, fish, and humans. The genus Erysipelothrix contains four species: E. rhusiopathiae (serotypes 1a, 1b, 2, 4, 5,6,8,9,11,12,15,16,17,19,21, and N), E. tonsillarum (serotypes 3, 7, 10, 14, 20, 22, and 23), Erysipelothrix sp. strain 1 (serotype 13), and Erysipelothrix sp.…”
mentioning
confidence: 99%
“…isolation from feces and other contaminated material, including intestinal lymphoid tissue, urine, nasal secretions, and decomposing animal tissue. 20 In addition, selective agar media including sodium azide crystal violet (SACV), also known as ''Packer's medium,'' 13 nalidixic acid medium, 1 and a modified blood azide agar 15 have also been described to aid in the isolation of Erysipelothrix spp. 4,5 A previous study 8 reported no significant difference in isolation frequency between blood azide agar and SACV medium.…”
mentioning
confidence: 99%
“…Recently, we reported that a cluster of avirulent serotype 7 strains found in porcine tonsils was genetically distinct from E rh.usiupathize7 and a new species was proposed for serotype 7 strains, Erysipelothrix tonsillarum (8). Moreover, serotypes 1 through 23 and type N of E. rhusiopathiae were studied, and two distinct DNA relatedness groups were identified on the basis of the results of DNA-DNA hybridization experiments performed with the type strains of these two species (9).…”
mentioning
confidence: 99%
“…Moreover, serotypes 1 through 23 and type N of E. rhusiopathiae were studied, and two distinct DNA relatedness groups were identified on the basis of the results of DNA-DNA hybridization experiments performed with the type strains of these two species (9). However, phenotypically, E. tonsillarum appeared to be identical to E. rhuswpathiae except that it was aMe to produce acid from saccharme (8,9).Since cell proteins are genetically directed, their electrophoretic patterns tend to express genetic relationships among microorganisms (7). The purposes of this study were to compare the electrophoretic patterns of whole-cell proteins from strains of E. rhusiopathiae and E. tonsillarum and to identify phenotypic characteristics that distinguish these two species.…”
mentioning
confidence: 99%